The effect on survival from the use of a saphenous vein graft during coronary bypass surgery: a large cohort study. (8th June 2018) - Royse, Alistair; Pawanis, Zulfayandi; Canty, David; Ou-Young, Jared; Eccleston, David; Ajani, Andrew; Reid, Christopher M; Bellomo, Rinaldo; Royse, Colin
Abstract: OBJECTIVES: Saphenous vein graft (SVG) remains the predominant conduit used in coronary surgery. The internal mammary artery has higher later term patency and confers superior survival. Current debate focuses on the increased use of arterial conduits rather than eradication of venous conduits. METHODS: Patient data extracted from the Australian and New Zealand Society of Cardiothoracic Surgeons database from 2001–2013 were linked to the national death registry held by the Australian Institute of Health and Welfare for all-cause mortality with censor date 7 October 2014. The dataset was divided according to use of SVG rather than the arterial conduit. Analyses of SVG ≥ 1 or SVG = 1 were compared to SVG = 0. Additionally, groups of 3, 4 or 5 grafts were subjected to multiple analyses testing the mortality hazard with increasing use of SVG. Propensity score matched analyses were conducted using 24 variables. RESULTS: Of 51 113 primary coronary surgery patients, unmatched survival at up to 12.5 years was significantly lower for SVG ≥ 1, n = 33 359, mortality hazard ratio (HR) 1.24 [95% confidence interval (CI) 1.18–1.30], P < 0.001; and for SVG = 1, mortality HR 1.19 (95% CI 1.12–1.26), P < 0.001. Similar results were present for the propensity score matched groups; SVG ≥ 1, n = 14 355 pairs, HR 1.22 (95% CI 1.15–1.30), P < 0.001; and for SVG = 1, n = 12 316 pairs, HR 1.22 (95% CI 1.14–1.30), P < 0.001. All matched analyses within restricted graft groups had increasing HR with increased number of SVG used. CONCLUSIONS: Any use of SVGs is independently associated with reduced survival after coronary artery bypass surgery.